2018
DOI: 10.1002/ps.5191
|View full text |Cite
|
Sign up to set email alerts
|

Dibutyl succinate, produced by an insect‐pathogenic fungus, Isaria javanica pf185, is a metabolite that controls of aphids and a fungal disease, anthracnose

Abstract: This is the first report indicating that a single metabolite, dibutyl succinate, from the beneficial fungus I. javanica, has potential for use in integrated pest management to inhibit both insect and fungal plant pathogens. © 2018 Society of Chemical Industry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
8
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 33 publications
1
8
0
1
Order By: Relevance
“…Its role was previously mentioned by several researchers who showed a temperature gap beyond it becomes harmful to the effectiveness of certain fungi [ 34 , 72 ]. However, the study revealed a reduction in diameter of the symptoms on the leaf, confirming prior results on C. Acutatum mycelial growth using I. javanica pf185 [ 66 ]. It is documented that IPM is the most important tool to sustainably keep fungal threats below the economic threshold, but several mechanisms participate to the control of crop enemies using endophytic fungi [ 73 ].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Its role was previously mentioned by several researchers who showed a temperature gap beyond it becomes harmful to the effectiveness of certain fungi [ 34 , 72 ]. However, the study revealed a reduction in diameter of the symptoms on the leaf, confirming prior results on C. Acutatum mycelial growth using I. javanica pf185 [ 66 ]. It is documented that IPM is the most important tool to sustainably keep fungal threats below the economic threshold, but several mechanisms participate to the control of crop enemies using endophytic fungi [ 73 ].…”
Section: Discussionsupporting
confidence: 88%
“…The results in Table 2 and Table 3 give a relative antifungal capacity in I. javanica pf185 against anthracnose transmitted by C. acutatum . Likewise, Lee [ 66 ], regarding the same entomopathogenic isolate, revealed the fungicidal action of both supernatant and its secondary metabolite dibutyl succinate on anthracnose caused by C. acutatum . However, their seven-day assessment only showed a weak efficacy of the compound against the pathogenic fungus under laboratory conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, we found that I. javanica pf04, had optimal conidia formation when grown under solid state fermentation on a barley substrate supplemented with silkworm powder and moth larvae [33]. The demonstration of antifungal activities in dual culture assays on PDA indicates that extracellular products are involved, and dibutyl succinate from pf185 was identified as a key metabolite for antifungal and aphicidal activity [35]. These findings accordingly support the possibility of the production of effective cross-kingdom metabolites by other entomopathogens [8,9].…”
mentioning
confidence: 99%
“…Beneficial fungi are very important to maintain the healthy growth of plants and improve plant productivity, a concept applied to many agricultural practices [ 18 , 26 , 35 ]. The effects of rhizosphere fungi on plant growth and productivity are direct or indirect.…”
Section: Discussionmentioning
confidence: 99%